2012
DOI: 10.1100/2012/585791
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of PM10by Positive Matrix Factorization in Urban Area of Mumbai, India

Abstract: Particulate Matter (PM10) has been one of the main air pollutants exceeding the ambient standards in most of the major cities in India. During last few years, receptor models such as Chemical Mass Balance, Positive Matrix Factorization (PMF), PCA–APCS and UNMIX have been used to provide solutions to the source identification and contributions which are accepted for developing effective and efficient air quality management plans. Each site poses different complexities while resolving PM10 contributions. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 27 publications
1
33
1
Order By: Relevance
“…PC1 showed a strong correlation among elements from natural origin, such as those from plant constituents (Ca, K, Mg, P and S) and from soil (Ba, Ca, Fe, K, Mg and Ti). These results are consistent with the plant's biochemistry, contrary to the EF values >2 that indicated anthropogenic influence (von Schneidemesser et al, 2010;Gupta et al, 2012).…”
Section: Statistical Analysis: Pca-mlra Applied To Leaves Datasetcontrasting
confidence: 45%
See 1 more Smart Citation
“…PC1 showed a strong correlation among elements from natural origin, such as those from plant constituents (Ca, K, Mg, P and S) and from soil (Ba, Ca, Fe, K, Mg and Ti). These results are consistent with the plant's biochemistry, contrary to the EF values >2 that indicated anthropogenic influence (von Schneidemesser et al, 2010;Gupta et al, 2012).…”
Section: Statistical Analysis: Pca-mlra Applied To Leaves Datasetcontrasting
confidence: 45%
“…The relationship among elements strongly suggests anthropogenic origin, considering that Cr, Cu, La, Pb, Sr and Zn (which do not appear in PC1) are moderately distributed among these PCs. These elements are mainly related to anthropogenic sources, as also indicated by EF > 2 (Quiterio et al, 2004;Guéguen et al, 2012;Godoy et al, 2009;Castilho et al, 2012;Gupta et al, 2012). Zinc is considered to be an indicator of waste burning (Gupta et al, 2012), industrial activity (Quiterio et al, 2004;Mateus et al, 2013), tire wear and brake linings (Khan et al, 2010).…”
Section: Statistical Analysis: Pca-mlra Applied To Leaves Datasetmentioning
confidence: 99%
“…While for the coarse particle four factos were recognized including marine aerosols, crustal/soil dust, nitrates and road side). Gupta et al (2012) reported the PM sources of various sites within Mumbai city using PMF. Industrial area of Mahul showed sources such as residual oil combustion and paved road dust, traffic, coal fired boiler and nitrate sources.…”
Section: Source Apportionmentmentioning
confidence: 99%
“…The ratio of Q true to Q robust is another parameter to evaluate the PMF modeled results. The Q robust is estimated excluding the outlier data which are samples having scaled residual greater than 4 and Q true is estimated including all the data points (Gupta et al, 2012;Waked et al, 2013). The ratio close to 1 indicates better solution and greater than 1.5 indicates influence of peak events on the model.…”
Section: Resultsmentioning
confidence: 99%